2021
DOI: 10.3329/jasbs.v47i2.57274
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Noise Pollution Levels In Dhanmondi Area, Dhaka: A Geospatial Analysis

Abstract: Noise pollution has been recognized as one of the most vital environmental pollutions that affecting urban area’s quality of life. Sound levels at different points of the study area have been recorded and presented spatially by geostatistical analysis. A comparison has been made between the study area data in 2019 and that of 2021. In 2021 the noise level was significantly higher despite the Covid 19 pandemic. The comparative study showed that the noise level of the study area in 2021increased significantly. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Immeasurable people in Bangladesh face several health risks due to sound pollution. Recent studies have shown that noise levels are higher at different points in the city center of Magura (Das et al, 2018), Chittagong (Uddin et al, 2018), Sylhet (Das and Basak, 2020), Khulna (Sultana et al, 2020), Mymensingh (Hasan et al, 2021), and Dhaka (Parvin, 2021). It is becoming an unreasonable intervention to slowly but surely impose human well-being, health (physical and psychological), and quality of life (Islam et al, 2015;Masoudzadeh et al, 2017, Oguntunde et al, 2019Sultana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Immeasurable people in Bangladesh face several health risks due to sound pollution. Recent studies have shown that noise levels are higher at different points in the city center of Magura (Das et al, 2018), Chittagong (Uddin et al, 2018), Sylhet (Das and Basak, 2020), Khulna (Sultana et al, 2020), Mymensingh (Hasan et al, 2021), and Dhaka (Parvin, 2021). It is becoming an unreasonable intervention to slowly but surely impose human well-being, health (physical and psychological), and quality of life (Islam et al, 2015;Masoudzadeh et al, 2017, Oguntunde et al, 2019Sultana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%